PAYMENT ACCOUNTING SYSTEM AT PT. XYZ IN BEKASI - edi ilham; Kustari (JACTA: Journal of Accounting and Tax, 2022)
The research is entitled Payroll Accounting System at PT. XYZ in Bekasi. This research aims to determine the flow of the payroll system and internal control at PT. XYZ in Bekasi. A good payroll system plays an important role in a company to increase employee effectiveness. The research method used is in the form of field studies using data collection techniques through observation and library research, namely by observing, interviewing directly how work and the applicable system work and studying in the form of written materials the payroll accounting system applied to PT. XYZ in Bekasi. Based on the results of the discussion shows that the payroll accounting system at PT. XYZ has a system that must be supplemented to meet the elements of internal control. There are still weaknesses, namely management does not carry out more supervision in the payroll section and management does not separate the authorization for recording clock cards with the personnel department.